2016
DOI: 10.5604/17331331.1197324
|View full text |Cite
|
Sign up to set email alerts
|

The Functions of Effector Proteins in Yersinia Virulence

Abstract: Yersinia species are bacterial pathogens that can cause plague and intestinal diseases after invading into human cells through the Three Secretion System (TTSS). The effect of pathogenesis is mediated by Yersinia outer proteins (Yop) and manifested as down-regulation of the cytokine genes expression by inhibiting nuclear factor-κ-gene binding (NF-κB) and mitogen-activated protein kinase (MAPK) pathways. In addition, its pathogenesis can also manipulate the disorder of host innate immune system and cell death s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Moreover, upregulation of YopJ, which dampens TLR-induced expression of proinflammatory cytokines by interference with the MAPK and NF k B pathways [ 64 , 65 ], and caspase-1 promoted IL-1β production [ 66 ], could overcome low translocation activity in the absence of CNF Y and help to dampen inflammation during persistence. However, this process is also accompanied by a decreased expression of other effectors such as YopE, YopH, YopM and YpkA [ 10 , 11 ] (Fig 8A ). These effectors were found to inhibit Rho GTPases and/or perturb host immune responses, including the production of certain pro-inflammatory cytokines, the maturation of caspases and the activation of the inflammasome [ 67 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, upregulation of YopJ, which dampens TLR-induced expression of proinflammatory cytokines by interference with the MAPK and NF k B pathways [ 64 , 65 ], and caspase-1 promoted IL-1β production [ 66 ], could overcome low translocation activity in the absence of CNF Y and help to dampen inflammation during persistence. However, this process is also accompanied by a decreased expression of other effectors such as YopE, YopH, YopM and YpkA [ 10 , 11 ] (Fig 8A ). These effectors were found to inhibit Rho GTPases and/or perturb host immune responses, including the production of certain pro-inflammatory cytokines, the maturation of caspases and the activation of the inflammasome [ 67 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them are important acute stage virulence genes, including the adhesins Ail and YadA, the cytotoxic necrotizing factor CNF Y , the virulence plasmid-encoded type III secretion system (T3SS) and the associated Yop effectors, which are highly upregulated during the initial phase of the infection [ 10 ]. The Yop effectors prevent phagocytosis by leukocytes, which is important for colonization and systemic dissemination [ 11 ]. The CNF Y toxin constitutively activates small Rho GTPases by deamidation and improves Yop translocation into host cells, thereby enhancing inflammation and tissue damage [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The essential effector YopM is a modulator of kinases PRK1 and PRK2. This modulation eventually leads to a reduction in pro-inflammatory cytokines lessening the effectivity of the host immune response [8]. YopM is the first effector to be recognized as a bacterial cell-penetrating protein as it can leave and re-enter host cells after translocation [127].…”
Section: Antibodies Targeting Extracellularly Available Effectorsmentioning
confidence: 99%
“…Some pathogens even interfere with or induce programmed cell death (Yersinia spp., Pseudomonas spp.) [8,9]. The T3SS is becoming an important anti-virulence target for many reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Haemodialysis patients are chronically iron deficient and iron supplementation is routinely administered to maintain an iron appropriate level. Iron is an essential growth factor of bacteria for multiplication in the host, and, on the contrary, evidences showed that iron supplementation is harmful for the host defence mechanisms, oxygen transport, deoxy ribonucleotide synthesis, and redox reactions (6,28,35). In haemodialysis patients, various authors reported high incidence of iron-overload (8,13,26).…”
Section: Introductionmentioning
confidence: 99%